The Potential of Electronic-Based Homeschooling: Integrating Applications to Create A Multidimensional Post-Pandemic Generation - Martoni Ira Malik; Sarah Seri Rahayu; Ro’aini Ro’aini (The Faculty of Teacher Training and Education The University of Jember Jember, Indonesia, 2020)
Homeschooling is a highly demanding learning process during the current pandemic. With this, it created an innovative product capable of shaping the pedagogical and psychosomatic students' potential during home study. Each learning activity is done through a remote system by leveraging the development of technology. The rise of nausea and demands in the student body is the basis for the solvency of the student body by forming the competence outside the school's learning materials. This learning application certainly leads to the creation of its superior generation with its distinctive interest traits affecting the profession. By using qualitative research methods and using a descriptive approach capable of describing online learning containers capable of increasing students' external potential. Thus, E-BASEKOLAH becomes one of the solutions that provides the potential to match students' interests. This alternative solution is a generation that able to create self-employment after the covid-19 pandemic.